MEDIA CONVERGENCE AND LINGUISTIC CHARACTERISTICS OF THE INTERNET SPACE IN MODERN CONDITIONS - V I Kostadinov; A E Bazanova (RUDN Journal of Studies in Literature and Journalism, 2016)
The article discusses the development of Internet-linguistics and the impact of media convergence on the language peculiarities of Internet environment. Particular attention is paid to the establishment and approval of Internet linguistics as a new direction in linguistics research, the methods it uses, terminological system, Internet discourse and peculiarities of Internet communications. The purpose of this publication is to try to summarize the described by the Russian and foreign scientists linguistic characteristics in the Internet with the influence of her media convergence and the consequences that result from their interaction. Analyzing and provides specific examples from the Internet, the author tries to show the interdependence and close relationship the key elements of the media environment, which led media linguistic in a separate direction, which deserves detailed study and attention of scientists.